Sense & Sensation: the Act of Mediation and its Effects - Wilson-Bokowiec, Julie; Bokowiec, Mark (Intermédialités / Intermediality, 2008)
AbstractWhat happens when we mediate? What are the effects of mediation on the body? Are we being altered by technology? This article examines the unique occurrence of cross-model perception found to be associated with moments of acute kinaesonic expression in real-time interactive digital performance. The function and significance of cross-model perception is discussed in the light of the author’s practice with the Bodycoder System and new research into bodily self-consciousness and the sensory effects of new technology within the area of the neurosciences. Empirical findings are framed by a broader theoretical discussion that draws on John Cage’s notion of organicity and Gilles Deleuze’s sensual description of seizure, in opposition to telecommunication’s threat to the morphological stability of reality proposed by Paul Virilio. The article argues that cross-model perceptions, sensory mislocations, compensatory and synaesthesic effects of increasingly intimate and significant couplings of humans and technologies may not, as feared, represent a loss or disruption of perceptual reality, but rather indicate the register of a hitherto unconscious human facility.